2021
DOI: 10.1088/1748-9326/abda6d
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of complex subsurface redox structures for sustainable development of agriculture and the environment

Abstract: Cost-efficient targeted nitrogen (N) regulation of agriculture with low impact on the environment is the new N regulation paradigm. It requires detailed knowledge on the geological and geochemical conditions of the subsurface that is crucial for assessing the nitrate flowpaths and reduction processes. An integral part of this is analysis of the subsurface redox structures to determine the locations of nitrate reduction. This knowledge has so far not been easy to access because of lacking technology. Here we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The groundwater table monitored at wells around the sampling points confirms that it drops down to 4 m bls and occasionally to 6 m bls in dry years (Supporting Information Figure S2). Madsen et al (2021) also reported a sharp transition from oxic to reduced conditions at around 4−6 m bls in clay till of the quaternary sequence. 22 Altogether, we postulate that the wetting−drying cycle may be responsible for developing the high-denitrification zone in clay till.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The groundwater table monitored at wells around the sampling points confirms that it drops down to 4 m bls and occasionally to 6 m bls in dry years (Supporting Information Figure S2). Madsen et al (2021) also reported a sharp transition from oxic to reduced conditions at around 4−6 m bls in clay till of the quaternary sequence. 22 Altogether, we postulate that the wetting−drying cycle may be responsible for developing the high-denitrification zone in clay till.…”
Section: Resultsmentioning
confidence: 88%
“…Based on the tTEM resistivity model, sediment color, and chemistry of water and the sediment, Madsen et al (2021) proposed that the redox architecture of the quaternary sequence displays a geological window type, while that of the buried valley is a planar type. 22,23 The top surface of the quaternary sequence is covered mainly by clay till with small patches of sandy till (Figure 1b).…”
Section: Methodsmentioning
confidence: 99%
“… 35 Denmark is not yet meeting the demands of both national and EU legislations, and more locally targeted mitigation measures are being developed to further lower the nitrate content in groundwater. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Some data are specifically gathered for this study (tTEM and new boreholes; see Fig. 1), while other existing data are freely available through the Danish borehole database "Jupiter" (Hansen and Pjetursson, 2011) and the Danish geophysical database for onshore data "GERDA" (Møller et al,Figure 1. The study area and available data, where (a) displays a digital terrain model, geophysical data and outlined TI areas, (b) an orthophoto (from Geodatastyrelsen, ortophoto forår, WMS Service, March 2021) and geochemical data, and (c) a surface geology map (1 m below surface, Jakobsen and Tougaard, 2020).…”
Section: Methodsmentioning
confidence: 99%